Computational Study of the Time-dependent Flow Field of a Water-Molasses Mixture Inside a Stirred Vessel - Suci Madhania; Tantular Nurtono; Sugeng Winardi; Yuswan Muharam; Widodo Wahyu Purwanto (International Journal of Technology, 2019)
Detailed information on the flow field in the operation of a mixing unit is necessary for the optimal design of the reactor. The flow field characteristic is an essential factor in obtaining an optimal stirred vessel design. The efficiency of the stirred vessel system depends on, for example, the stirred vessel geometry, the flow induced by the impeller, the working fluid properties and the operating condition. The aim of this study is to exhibit the time-dependent flow field of the mixing process inside a stirred vessel for different propeller rotational speeds using computational fluid dynamics methods. The working fluid in question is molasses and water, which is a miscible liquid. The stirred vessel is a conical-bottomed cylindrical vessel (D = 0.28 m and H = 0.395 m) equipped with a three-blade propeller (d = 0.036 m). The transient calculation was conducted using ANSYS Fluent version 18.2. The Mixture multiphase flow model coupled with the Reynolds-averaged Navier-Stokes Standard k-? (SKE) turbulence model was applied to capture the information on the time-dependent flow fields at various propeller rotational speeds inside the stirred vessel. The flow generated by the propeller was compared at 1000 rpm, 1300 rpm and 1500 rpm. The Multiple Reference Frame method was used to solve the moving domain and stationary domain multiple frames case. The results revealed the local velocity, flow pattern, molasses volume fraction value, density gradient distribution, power number and flow number. The profile of all the variables determines the optimal operating conditions for the degree of mixing required.